2006
DOI: 10.1108/00035590610678910
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of zinc in alcohol‐water solvents

Abstract: PurposeThe aim of this paper is to elucidate the mechanism and the effect of different monohydric organic solvent on the corrosion behaviour of zinc in distilled water.Design/methodology/approachThe corrosion behaviour of zinc in stagnant distilled water containing 0‐70 percent (v/v) methanol, ethanol or n‐propanol was investigated at 25‐40°C using potentiodynamic polarization technique. The activation parameters that govern zinc corrosion in mixed solvent system were also calculated.FindingsThe data revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…To avoid the corrosion of metals, many methods have been designed after analyzing the different forms of corrosion 2 . These methods include: inhibitors, electrical protection, surface coating, equipment design, and material selection 6 . Inhibitors are chemicals that, when applied in tiny amounts to corrosive conditions, inhibit electrochemical corrosion processes on metal surfaces 1 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the corrosion of metals, many methods have been designed after analyzing the different forms of corrosion 2 . These methods include: inhibitors, electrical protection, surface coating, equipment design, and material selection 6 . Inhibitors are chemicals that, when applied in tiny amounts to corrosive conditions, inhibit electrochemical corrosion processes on metal surfaces 1 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Such results are in agreement with previous ones that showed that the amount of water and pH of many organic liquids are related to the corrosion of zinc. In fact, this metal is attacked rapidly when high content of water is present because of the lack of access to oxygen and due to the stabilization of corrosion products by water molecules [15,16]. Only in aluminum alloys (Figures 3 and 4), solution 4 was less corrosive than 3, probably due to the passivation of such materials.…”
Section: Methodsmentioning
confidence: 99%